PELATIHAN PEMBUATAN SOAL TEST MENGGUNAKAN APLIKASI GOOGLE FORM - Heri Yugaswara; Suhaeri Suhaeri; Herika Hayurani (Info Abdi Cendekia, 2020)
Cilebut 5 State Elementary School is an elementary school on Jalan Cilebut Barat Village, Sukaraja District, Bogor Regency. Some teachers have difficulty teaching online which is their task such as making online questions, so training is needed on how to make online test questions. The training provided was the creation of online questions using the Google Form application provided by Google. The activity method consists of 3 stages, namely the planning, implementation and evaluation stages. The planning stage includes team preparation, scheduling, participant and facilitator preparation. After training, each participant is given a test to measure his post-training ability. The test results of 72% of the activity participants were successful in the Google Form application training in making questions.